2010
DOI: 10.1088/0953-4075/43/11/111001
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy of sequential three-photon double ionization of Ar irradiated by EUV free-electron laser pulses

Abstract: We have investigated the ionization of the Ar atom by 51 nm extreme-ultraviolet light pulses at the free-electron laser facility, SPring-8 Compact SASE Source test accelerator, in Japan. The angle-resolved photoelectron spectra contain lines due to sequential three-photon double ionization with the second ionization step proceeding via the resonantly enhanced two-photon absorption. The relative intensities of the corresponding photoelectron peaks and their angular dependence are explained in the framework of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…Recently, pioneering experimental reports on resonance multiphoton ionization of atoms by strong EUV FEL lights have appeared [12][13][14][15][16]. Among these studies Miyauchi et al [14] and Sato et al [16] have revealed that the ionization probability deviates strongly from the conventional I n scaling for nonresonance multiphoton ionization.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pioneering experimental reports on resonance multiphoton ionization of atoms by strong EUV FEL lights have appeared [12][13][14][15][16]. Among these studies Miyauchi et al [14] and Sato et al [16] have revealed that the ionization probability deviates strongly from the conventional I n scaling for nonresonance multiphoton ionization.…”
Section: Introductionmentioning
confidence: 99%
“…The spectrum of the FEL pulse can overlap the position of one or several excited intermediate-ion states thus leading to resonant enhancement of the 3PDI [64][65][66].…”
Section: Pads In Sequential 3pdimentioning
confidence: 99%
“…For the resonantly enhanced sequential 3PDI, a simple three-step mechanism was first implied [64], when after the first-step ionization (1), the second photon excites one or several discrete states, depending on the spectral profile of the pulse, while the third photon ionizes the excited and generally polarized ion. Such an approach allowed to explain observed angle-resolved photoelectron spectra in Ar around 20 eV kinetic electron energy, produced by FEL facility SPring-8 Compact SASE Source test accelerator (Japan) with the photon energies of 24.18-24.70 eV [64].…”
Section: Pads In Sequential 3pdimentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical description is based on a recently developed stepwise ionization model, where each subsequent photon interacts with an ionic intermediate state formed at a preceding step. This approach, in combination with the statistical tensor formalism [19], was previously successfully applied to sequential 2PDI from the outer p shells of noble gas atoms [8,20,21] and three-photon resonantly enhanced sequential double ionization of argon [22]. Within this model, anisotropy in the photoelectron emission and alignment of the intermediate states are fully taken into account.…”
mentioning
confidence: 99%